2017
DOI: 10.2174/1874104501711010092
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolyl Pyrazoline Carbaldehydes as Enoyl-ACP Reductase Inhibitors: Design, Synthesis and Antitubercular Activity

Abstract: Introduction:In efforts to develop new antitubercular (anti-TB) compounds, herein we describe cytotoxic evaluation of 15 newly synthesized pyrrolyl pyrazoline carbaldehydes.Method & Materials:Surflex-Docking method was used to study binding modes of the compounds at the active site of the enzyme enoyl ACP reductase from Mycobacterium tuberculosis (M. tuberculosis), which plays an important role in FAS-II biosynthetic pathway of M. tuberculosis and also it is an important target for designing novel anti-TB agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Replacement of the methoxy group (26 and 28) with either F (30) or Cl (31) resulted in a drop in the antioxidant activity, which suggested that electron-donating groups are favored at positions 2 on the phenyl ring. A similar phenomenon was observed in the dihydropyrazole series (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Compound 43 was found to have an IC 50 of 6 µg/mL and was the most potent in this series.…”
Section: Antioxidant Activitysupporting
confidence: 76%
See 2 more Smart Citations
“…Replacement of the methoxy group (26 and 28) with either F (30) or Cl (31) resulted in a drop in the antioxidant activity, which suggested that electron-donating groups are favored at positions 2 on the phenyl ring. A similar phenomenon was observed in the dihydropyrazole series (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Compound 43 was found to have an IC 50 of 6 µg/mL and was the most potent in this series.…”
Section: Antioxidant Activitysupporting
confidence: 76%
“…The crude precipitate was recrystallized using chloroform to afford chalcones 17-31. The target dihydropyrazoles (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) were obtained by treating the synthesized chalcones with semicarbazide in a catalytic amount of pyridine and purified using silica gel column chromatography.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrazolines possess sundry of activities including antimicrobial [7][8][9], anticancer [10][11][12], antioxidant [13], antiamoebic [14], antiinflammatory [15], antidiabetic [16], diuretic [17] and carbonic anhydrase inhibition [18]. One of the extensively studied activities of dihydropyrazole-1-carboxamides is their antitubercular ability against different Mycobacterium species [19][20][21][22][23][24]. This may be due to the fact that the pyrazoline contains carbohydrazide portion which is also found in the most commonly used antitubercular drug, Isoniazid.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Corbett et al reported that the emergence of anti-TB resistance and HIV are vital contributors to death by TB [3]. Recently, several drugs in the market were used for TB treatment, including isoniazid (INH), rifampicin, pyrazinamide, and delamanid, all of which possess a nitrogen atom in their ring structure [4]. The problem is commonly known that Mycobacterium tuberculosis (MTB) has developed resistance to any of these drugs [5].…”
Section: ■ Introductionmentioning
confidence: 99%